CATALOGIC 301C model – validation and improvement. Issue 6 (3rd June 2017) - Dimitrova, N. H.; Dermen, I. A.; Todorova, N. D.; Vasilev, K. G.; Dimitrov, S. D.; Mekenyan, O. G.; Ikenaga, Y.; Aoyagi, T.; Zaitsu, Y.; Hamaguchi, C.
Abstract: In Europe, REACH legislation encourages the use of alternative in silico methods such as (Q)SAR models. According to the recent progress of Chemical Substances Control Law (CSCL) in Japan, (Q)SAR predictions are also utilized as supporting evidence for the assessment of bioaccumulation potential of chemicals along with read across. Currently, the effective use of read across and QSARs is examined for other hazards, including biodegradability. This paper describes the results of external validation and improvement of CATALOGIC 301C model based on more than 1000 tested new chemical substances of the publication schedule under CSCL. CATALOGIC 301C model meets all REACH requirements to be used for biodegradability assessment. The model formalism built on scientific understanding for the microbial degradation of chemicals has a well-defined and transparent applicability domain. The model predictions are adequate for the evaluation of the ready degradability of chemicals.